Stratigraphy and Tectonic Development of Mentawai Islands, West Sumatera, Based on Plate Tectonic Theory - S Andi Mangga; Kusnama Kusnama; Suyono Suyono (Jurnal Geologi dan Sumberdaya Mineral, 2006)
The Mentawai Islands are situated on the Indian Ocean westwards of West Sumatera Province forming a non-volcanic island arc. Stratigraphic and tectonic development of the islands are strongly related to the subduction between the Indian Ocean and Eurasian Continental Plate. Tectonic activities have occurred since Early Tertiary - Late Pliocene. It has happened simultaneously with the Indian Ocean Plates collision moving northwards and subducted below the Sunda/Eurasian Continental Plate. The Ophiolite and Melange Complexes were exposed and overlain unconformably by the acceleration prism of sedimentary rocks (Mentawai Group) formed as a pond sedimentation deposited within a small basin situated between active thrust fault fragments. Based on the age determination gained from paleontological analysis, tectonic configuration, basin development, and sedimentation rate, the Mentawai Islands are believed to be formed by mélange complexes comprising part of an uplifted accretionary complex of a non-volcanic island arc. Keywords: stratigraphy, tectonic, mélange, Mentawai Islands